Teaching technology awareness: capabilities and thresholds to think about technology - Sneltvedt, Ole; Geirbo, Hanne Cecilie; Haagensen, Trine Krigsvoll (Frontiers in Education, 2025)
Technological advances are blurring the boundaries between technical and non-technical disciplines. This shift compels educators to develop teaching methods that equip students with the capabilities necessary to be aware of technological impact and investigate the meaning of technologies throughout their careers. Here, we address the challenge of teaching technology awareness in non-technical disciplines. We do so by presenting an account of the development of the course Technology and Society at Oslo Metropolitan University. Alongside providing insights into the curriculum design and evolution of this course, we offer a theoretical contribution. Specifically, we highlight the benefits of a capabilities-oriented curriculum design and the use of threshold concepts as tools to enhance students’ technological awareness, understood as the ability to interpret the meaning of technology within their future professions. We conclude by presenting an example from teaching that demonstrates how technology can challenge the meaning of professional practice. In doing so, we show how professional practice, in turn, influence the meaning of technology, fostering a deeper understanding of its role and impact.